Penguatan Kompetensi Pedagogik Guru SMK YPM Tuban dalam Mendukung Kesejahteraan Peserta Didik melalui Inovasi Pembelajaran di Era Society 5.0 - Mardi Widodo; Mario Fahmi Syahrial; Dwi Wahyu Kartikasari; Gusti Uripno; Kumaidi Kumaidi (Jurnal Medika: Medika, 2026)
This community service program aims to strengthen teachers’ pedagogical competence at SMK YPM Tuban in designing and implementing active, contextual, and skill-oriented learning in the era of 21st-century education. The program employed an integrated approach consisting of pedagogical workshops, demonstration of learning models, structured microteaching sessions, and on-the-job mentoring for three weeks after the training. A total of 44 teachers from both vocational and general subject areas participated, fostering interdisciplinary collaboration and accelerating the adoption of innovative teaching practices. The initial assessment revealed a mean pedagogical competence score of 60, with only 28% of teachers consistently applying active learning strategies. Based on these findings, the intervention was designed by combining theoretical knowledge with practical application and continuous feedback. Microteaching served as the core strategy, enabling teachers to practice teaching, receive structured observations, and reflect on their performance. The evaluation results indicated a significant improvement, with the average post-test score increasing to 85 and 91% of teachers achieving competency standards. Participant satisfaction reached 4.6 out of 5, reflecting a highly positive response to the program. Additionally, there was a substantial increase in the implementation of active learning strategies and the use of contextual lesson plans aligned with the Merdeka Curriculum. Qualitative findings highlight that the success of the program was supported by reflective microteaching practices, intensive classroom mentoring, and strong institutional support. However, challenges such as varying initial competencies and limited time for lesson planning were identified. Overall, this program proved effective in enhancing teachers’ pedagogical competence and bridging the gap between theory and classroom practice, with strong potential for sustainability through continuous mentoring and professional learning communities.